2022
DOI: 10.1007/s11356-022-20316-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the environmental Kuznets curve hypothesis and role of carbon emission policies in the case of Russian Federation

Abstract: Climate change currently observed and expected in the future is associated with risks to security and sustainable development and natural and irreversible consequences. To minimize these risks, it is necessary to adapt the public administration, economic sectors, and regional infrastructure to the changing climate conditions. This paper discovers the links between CO 2 emissions and their key determinants such as economic growth, energy consumption, population, trade openness, and financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…However, it causes less CO 2 emissions later on. Similarly, in the study by (Akadiri et al 2021 ) for BRICS countries, in the study by Adebayo ( 2021 ) for Indonesia, in the study by Jian et al ( 2022 ) for West African countries, in the study by Ali et al ( 2021 ) for Pakistan, in the study by Genc et al ( 2022 ) for Turkey, Kilinc-Ata and Likhachev ( 2022 ) found that the EKC hypothesis was valid for Russia and Zeraibi et al ( 2022 ) for the Chinese economy. Therefore, in these studies, economic growth increases environmental pollution up to a certain point and then causes environmental degradation to increase gradually.…”
Section: An Overview Of the Literature Within The Framework Of The Us...mentioning
confidence: 89%
“…However, it causes less CO 2 emissions later on. Similarly, in the study by (Akadiri et al 2021 ) for BRICS countries, in the study by Adebayo ( 2021 ) for Indonesia, in the study by Jian et al ( 2022 ) for West African countries, in the study by Ali et al ( 2021 ) for Pakistan, in the study by Genc et al ( 2022 ) for Turkey, Kilinc-Ata and Likhachev ( 2022 ) found that the EKC hypothesis was valid for Russia and Zeraibi et al ( 2022 ) for the Chinese economy. Therefore, in these studies, economic growth increases environmental pollution up to a certain point and then causes environmental degradation to increase gradually.…”
Section: An Overview Of the Literature Within The Framework Of The Us...mentioning
confidence: 89%
“…The relationship between carbon emissions and economic growth has been studied from the perspective of the environmental Kuznets curve in a large amount of literature ( 46 , 47 ). Nevertheless, there is a lack of studies on the relationship between embodied carbon emissions and economic growth due to regional trade in the context of the increasing developmental linkages and the close inter-regional trade of inputs and outputs in China.…”
Section: Methods and Datamentioning
confidence: 99%
“…According to the literature review (e.g., Saqib et al [1]; Ike et al [27]; Khan et al [31]; Leitão et al [6]; Ata and Likhachev [47]), it is possible to observe that international trade and foreign direct investment may have a positive (pollution haven hypothesis) or negative (pollution halo hypothesis) association with carbon dioxide emissions.…”
Section: H2 Do Renewable Energies Improve Environmental Degradation I...mentioning
confidence: 99%